Intestinal parasitism and socio-environmental factors among Mbyá-Guarani indians, Porto Alegre, Rio Grande do Sul, Brazil - Brandelli, Clara Lia Costa; Carli, Geraldo Attilio de; Macedo, Alexandre José; Tasca, Tiana (Revista do Instituto de Medicina Tropical de São Paulo, 2012)
Disturbing data reveal the prevalence of intestinal parasites and their relationship with socio-environmental factors among Mbyá-Guarani Indians. The prevalence was determined by spontaneous sedimentation in water, centrifugation-floatation, and Kato-Katz. A socioeconomic questionnaire was submitted to each family. The overall prevalence of intestinal parasites was 88.7%, and 45.5% were polyparasitized. There was 90.5% prevalence of enteric parasites in children (1-12- year-old), and 85% among 13-65-year-old individuals, indicating that both age groups are extensively parasitized. The parasite load was low to moderate for geohelminths and 75% of the families did not have latrine, thus the practice of defecation occurred outdoors. These findings suggest that the multiple intestinal parasitism in the Mbyá-Guarani community is high to the point of being the rule, and that it relates essentially to the traditional lifestyle and health habits. It is urgently necessary to implement the association of anti-parasitic treatment with sanitation improvement. This should be done simultaneously with health education activities for this population.